Is previous disaster experience a good predictor for disaster preparedness in extreme poverty households in remote Muslim minority based community in China? - Chan, E; Kim, J; Lin, C; Cheung, E; Lee, P (Springer US, 2014)
Disaster preparedness is an important preventive strategy for protecting health and mitigating adverse health effects of unforeseen disasters. A multi-site based ethnic minority project (2009-2015) is set up to examine health and disaster preparedness related issues in remote, rural, disaster prone communities in China. The primary objective of this reported study is to examine if previous disaster experience significantly increases household disaster preparedness levels in remote villages in China. A cross-sectional, household survey was conducted in January 2011 in Gansu Province, in a predominately Hui minority-based village. Factors related to disaster preparedness were explored using quantitative methods. Two focus groups were also conducted to provide additional contextual explanations to the quantitative findings of this study. The village household response rate was 62.4 % (n = 133). Although previous disaster exposure was significantly associated with perception of living in a high disaster risk area (OR = 6.16), only 10.7 % households possessed a disaster emergency kit. Of note, for households with members who had non-communicable diseases, 9.6 % had prepared extra medications to sustain clinical management of their chronic conditions. This is the first study that examined disaster preparedness in an ethnic minority population in remote communities in rural China. Our results indicate the need of disaster mitigation education to promote preparedness in remote, resource-poor communities.